24 INNERVATION AND REMODELING OF CERVIX WITH PARTURITION. (1st January 2006) - Boyd, J.; Ebner, C.; DeLeon, K.; Groves, M.; Yellon, S. M.; Kirby, M.
Abstract : Introduction: As part of the mechanism of birth, remodeling of the cervix involves an inflammatory process that mediates collagen degradation (Yellon and Kirby, JSGI 2003;10:323-38). In contrast to the uterus, the cervix is densely innervated as pregnancy nears term (Owman, Ciba Found Symp 1981;83:252; Kirby et al, JSGI in press). Whether pelvic nerve signaling is essential for ripening the cervix or parturition is controversial in rodents (Higuchi et al, Exp Neurol 1987;96:443; Burden et al, Anat Embryol 1990;182:449). Hypothesis: Transection of the pelvic nerve blocks ripening of the cervix, forestalling parturition. Methods: Long Evans rats in an IACUC-approved protocol were used for this study ( n = 7, Harlan Sprague Dawley, San Diego, CA). On day 14 of pregnancy, the pelvic nerve was transected ( n = 4); sham neurectomized pregnant rats ( n = 1) and nonpregnant rats ( n = 2) will serve as controls. On gestational day 25 of pregnancy, rats were deeply anesthetized and perfused through the heart. The paraformaldehyde-fixed cervix was paraffin embedded, sectioned at 10 μm, and processed for immunohistochemistry for immune cells and nerve fibers. Sections were counterstained with crystal violet and evaluated by brightfield microscopy. Results: Among the pregnant pelvic neurectomized rats ( n = 4), two exhibited dystocia up to gestational day 25, one delivered on day 22 with some reabsorption, and one delivered on gestational day 22 without reabsorption. The pregnant sham pelvic neurectomized rat delivered on day 24, birthing 3 pups with one reabsorption in the left uterine horn. All processed tissues have demonstrated leukocyte infiltration, although the pelvic neurectomized rats demonstrated substantially less than their sham counterparts. Conclusion: While this study is not yet completed, preliminary data for the Long Evans rat support the hypothesis that the pelvic nerve does indeed participate in initiating cervical remodeling via an inflammatory process. This is demonstrated by the lack of leukocytic infiltration present in each pelvic neurectomized rat. Although only two rats experienced a significant delay in parturition, an increase in sample size should demonstrate the expected dystocia more significantly. The present and future data from this study indicate the possibility that manipulating the signal sent by the pelvic nerve may be useful in preventing preterm birth. Supported by the dean of Loma Linda University School of Medicine.